Zooming with Babies: Troubling a Shared Present - Boycott-Garnett, Ruth (Journal of Childhood Studies, 2023)
This paper outlines how the specific constraints of virtual communication technology have stirred new thinking around what kind of research and what knowledge is produced with babies. During Zoom sessions, the 2–4-month-old babies were frequently present but out of shot, or glimpsed as a small limb or movement or sound on the other side of the screen. The babies’ bodies, movements, and sounds exceeded the boundaries of the screen. Through a posthuman lens, presence, time, and agency unravel the Zoom screen as an active participant that interferes with what can happen in a shared present in a liminal space.